Sunday

April 20, 2014

April 20, 2014

Posted by **kawn** on Friday, November 11, 2011 at 1:36pm.

(a) f + g (b) f – g (c)f*g(d)f/g

Please show all of your work.

f(x) = 5x^2-5

g(x) = x – 7

- precalculus -
**Steve**, Friday, November 11, 2011 at 2:50pmWhat's teh problem? Just substitute for f and g:

(c) f*g = (5x^2-5)(x-7) = 5(x-1)^2(x-7) = x^3 - 9x^2 + 15x - 7

**Related Questions**

maths - rewrite the addition sum given below using digits. Each letter is used ...

maths-urgent - rewrite the addition sum given below using digits. Each letter is...

maths-urgent - rewrite the addition sum given below using digits. Each letter is...

precalculus - Find the inverse of the function below. Graph the function below ...

PreCalculus - many questions. I have Given f(x) = x^5 and g(x) = 5+x , find (g o...

Precalculus - Given sinx= -1/8 and tanx<0. find sin2x

Precalculus - find (f composed of g)(x)=given f(x)=2x squared +3 g(x)=4x cubed +...

precalculus - Given sina= 3/4 and cosB = (-5)/13 and this is Quad II find cos(a...

precalculus - Find (a) the equation of a line that is parallel to the given ...

precalculus - Find the nth term of a sequence whose first several terms are ...